KONDISI TENAGA KERJA PENYANDANG DISABILITAS : TANTANGAN DALAM MEWUJUDKAN SUSTAINABLE DEVELOPMENT GOALS - Winsherly Tan (RechtIdee, 2021)
Sustainable development or commonly called Sustainable Development Goals (SDGs) is a goal achieved by many countries, including Indonesia. One of the goals of the SDGs is to create jobs for all parties without exception. Then the principle used in the SDGs is "no one leaves". This is a challenge for the Indonesian state to create jobs for all, including people with disabilities. However, the data shows that the workforce for people with disabilities is still low. The purpose of this research is to analyze the implementation of the right to work for persons with disabilities in Indonesia.The research method used in this research is normative juridical. The type of data used is secondary data which consists of primary legal material, namely the 1945 Constitution and Law Number 8 of 2016 concerning Persons with Disabilities and uses the Law Effectiveness Theory from Soerjono Soekanto.The results of this study indicate that the implementation of the fulfillment of the right to work for persons with disabilities has increased quite well from 2016 to 2020, but it is still not optimal and effective due to several factors, including legal factors, law enforcement, society and culture.